UNDERSTANDING PAKISTAN THROUGH LITERATURE: AN APPRAISAL OF SOME RECENT WORKS - Tauseef Ahmad Parray (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Pakistan, the second most populous Muslim country after Indonesia, came into existence on 14th August, 1947, after the division of ‘British ruled’ India (into India and Pakistan). From its inception to present, Pakistan covers a tumultuous history of over seven decades (1947-2019). Among the South Asian countries, no quantum of scholarship has been produced on any country—its history, religion (and religious ideology), politics, society, economy, and other inter-related issue—than Pakistan. This has continued in the last as well as present century. From 2010 onwards, numerous works have been published on religion, politics, military, and other aspects of Pakistan. This review essay, in this framework, presents an assessment of three (3) important works, published in between 2012 and 2014, so that to get clues of the various aspects of Pakistan. Following a descriptive-cum-comparative methodological approach, the books assessed and examined are: Ian Talbot, Pakistan: A New History (2012); Faisal Devji, Muslim Zion: Pakistan as a Political Idea (2013); and Aqil Shah, The Army and Democracy: Military Politics in Pakistan (2014). This assessment helps us in understanding the diverse scholarly approaches adopted (by different scholars) in studying Pakistan. The major argument put forth is that such an appraisal helps us not only in understanding the history of Pakistan, but in analyzing the issues and challenges Pakistan has faced, and is facing—be they religious, political, or related to military and security, etc.